Germline and Somatic Transformation of Mating Tetrahymena Thermophila by Particle Bombardment - Cassidy-Hanley, D. (1997)
Mating Tetrahymena thermophila were bombarded with ribosomal DNA-coated particles at various times in development. Both macronuclear and micronuclear transformants were recovered. Optimal developmental stages for transformation occurred during meiosis for the micronucleus and during anlagen formation for the macronucleus. Evidence is given for transient retention of the introduced plasmid. Genetic and molecular tests confirmed that sexually heritable transformation was associated with integration at the homologous site in the recipient micronuclear chromosome.